Probiotics and nanoparticle-mediated nutrient delivery in the management of transfusion-supported diseases - Han, Wendao; Xiong, Nating; Huang, Lingmei (Frontiers in Cellular and Infection Microbiology, 2025)
Bone marrow is vital for hematopoiesis, producing blood cells essential for oxygen transport, immune defense, and clotting. However, disorders like leukemia, lymphoma, aplastic anemia, and myelodysplastic syndromes can severely disrupt its function, leading to life-threatening complications. Traditional treatments, including chemotherapy and stem cell transplants, have significantly improved patient outcomes but are often associated with severe side effects and limitations, necessitating the exploration of safer, more targeted therapeutic strategies. Nanotechnology has emerged as a promising approach for addressing these challenges, particularly in the delivery of nutraceuticals—bioactive compounds derived from food sources with potential therapeutic benefits. Despite their promise, nutraceuticals often face clinical limitations due to poor bioavailability, instability, and inefficient delivery to target sites. Nanoparticles offer a viable solution by enhancing the stability, absorption, and targeted transport of nutraceuticals to bone marrow while minimizing systemic side effects. This study explores a range of bone marrow disorders, conventional treatment modalities, and the potential of nanoparticles to enhance nutraceutical-based therapies. By improving targeted delivery and therapeutic efficacy, nanoparticles could revolutionize bone marrow disease management, providing patients with more effective and less invasive treatment options. These advancements represent a significant step toward safer and more efficient therapeutic approaches, ultimately improving patient prognosis and overall health.